Musculoskeletal Models in a Clinical Perspective - Frigo, Carlo Albino (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book includes a selection of papers showing the potential of the dynamic modelling approach to treat problems related to the musculoskeletal system. The state-of-the-art is presented in a review article and in a perspective paper, and several examples of application in different clinical problems are provided.